2000
DOI: 10.1164/ajrccm.162.4.9808092
|View full text |Cite
|
Sign up to set email alerts
|

Tromethamine Buffer Modifies the Depressant Effect of Permissive Hypercapnia on Myocardial Contractility in Patients with Acute Respiratory Distress Syndrome

Abstract: In patients with acute respiratory distress syndrome (ARDS), permissive hypercapnia is a strategy to decrease airway pressures to prevent ventilator-induced lung damage by lowering tidal volumes and tolerating higher arterial carbon dioxide tension. However, in experimental studies hypercapnia impairs myocardial contractility and hemodynamic function. We investigated the effect of short-term permissive hypercapnia on myocardial contractility and hemodynamics in patients with ARDS. We hypothesized that the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 24 publications
6
75
1
5
Order By: Relevance
“…with ARDS. 46 In addition, our previous study (unpublished data) also demonstrated that moderating hypercapnic acidosis (PaCO 2 of 80-100 mm Hg) could result in the improving oxygenation, histologic characteristics, and a lessened inflammatory response, compared with severe hypercapnic acidosis (PaCO 2 of 130-150 mm Hg). A previous study has also shown that the beneficial effects of moderating hypercapnia may be offset by the high level of adverse effects caused by itself.…”
Section: Discussionmentioning
confidence: 89%
“…with ARDS. 46 In addition, our previous study (unpublished data) also demonstrated that moderating hypercapnic acidosis (PaCO 2 of 80-100 mm Hg) could result in the improving oxygenation, histologic characteristics, and a lessened inflammatory response, compared with severe hypercapnic acidosis (PaCO 2 of 130-150 mm Hg). A previous study has also shown that the beneficial effects of moderating hypercapnia may be offset by the high level of adverse effects caused by itself.…”
Section: Discussionmentioning
confidence: 89%
“…There is strong animal data suggesting the many potential benefits of hypercapnic acidosis (3,11,22,24), recently augmented by secondary analysis of the ARDSNet data (12). On the other hand, skepticism persists among some, with experimental and clinical data touting drawbacks to hypercapnic acidosis (16) and benefits of various buffering strategies (17,23,28), with some compelling clinical arguments for the use of THAM.…”
Section: Discussionmentioning
confidence: 99%
“…Not all investigators have reported benefit from hypercapnia, which has been implicated in pulmonary (6,16,17) and extrapulmonary (21,28) organ dysfunction, findings that have likely spurred further interest in the use of buffers. Bicarbonate buffers react to liberate carbon dioxide, which, because of high membrane permeability, may raise concern for further intracellular acidosis (9), a potentially operative, although unproven, mechanism in studies demonstrating worsened lung barrier function with buffering of hypercapnic acidosis (13,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Through more effectively correcting pH, THAM can also mitigate the adverse effects of acidosis on the cardiovascular system and restore hemodynamic stability. 57 …”
Section: Buffering Hypercapnic Acidosismentioning
confidence: 99%